Development of Infographic Media to the Character of Procrastination in Fine Arts Learning in Elementary School - Nurhaj, Lutvia; Yuliyanto, Aan; Hadianti, Yeni; Fauzan, Ahmad; Risliyani, Iis Novia; Kholish , Faiq Khafidz (International Conference on Elementary Education, 2025)
Infographic media is a visual presentation of information, data, or knowledge that aims to convey a message clearly and attractively. In the context of education, especially to reduce the character of procrastination of elementary school students, this media functions to increase interest in learning by using visual elements that attract students' attention. In addition, infographic media helps convey practical time management strategies and make students aware of the procrastination behaviors they perform. This research uses the Research and Development (R&D) method to develop infographic media that is designed to make learning more interesting and motivate students to be actively involved. Through literature review, this study analyzes various studies on the effectiveness of infographics in improving understanding and conveying information efficiently. The results of the analysis show that several obstacles in art learning, such as excessive content planning, complicated design, unstructured activities, lack of deadlines, lack of feedback, technological disruptions, and lack of self-evaluation, can increase procrastination. Therefore, effectively managing these aspects is essential to encourage task completion and reduce delays.